Hubungan Air dan Sanitasi Lingkungan dengan Kejadian Stunting pada Balita: Systematic Review - Sufia Rahmi, Indah; Abdul Razak; Elsa Yuniarti; Linda Handayuni (CV. CENDIKIA JENIUS INDONESIA, 2024)
Stunting is a growth and development disorder in children caused by chronic malnutrition and recurrent infections, and is characterized by height or height below normal. The short-term impact of stunting can be reduced learning ability due to lack of cognitive development. Stunting is a nutritional problem caused by multifactors, namely social factors, biological factors and environmental factors. Environmental conditions such as poor water and sanitation are indirect factors that cause stunting in children. This research aims to analyze the factors that influence stunting in toddlers. The research design used was the literature review method. A total of 20 articles from the Google Scholar database were reviewed in this research with criteria published in 2019-2023. This study was prepared using a narrative method. Articles were grouped with similar results to answer research questions. This study found that theoretically, sanitation and water quality have an influence on the occurrence of stunting events. Conclusion: In overcoming stunting, environmental factors must be considered to improve the quality of drinking water so that it meets health standards and is suitable and safe for consumption. It is recommended to maintain good sanitation to prevent the emergence of disease outbreaks which increase the number of illnesses and deaths.